Emergency right hepatectomy for a rare presentation of hepatic adenoma - Riyaz, Mohammad; Kamal, Harshit; Jeswanth, Satyanesan (International Surgery Journal, 2023)
We describe a unique case of a 65-year-old woman who had a hepatic adenoma compressing her right lung, inferior vena cava, and right ventricle, which had been the cause of her breathing problems, which had been becoming worse for the preceding six months. Through a right thoracoabdominal incision, an urgent right hepatectomy was carried out to manage her condition.